Comparative influence of bleeding and ischemic risk factors on diabetic patients undergoing percutaneous coronary intervention with everolimus‐eluting stents. Issue 6 (10th October 2020) - Goel, Ridhima; Cao, Davide; Chandiramani, Rishi; Roumeliotis, Anastasios; Blum, Moritz; Bhatt, Deepak L.; Angiolillo, Dominick J.; Ge, Junbo; Seth, Ashok; Saito, Shigeru; Krucoff, Mitchell; Kozuma, Ken; et al.
Abstract: Objective: To investigate the impact of ischemic and bleeding risk factors on long‐term clinical outcomes of patients with diabetes mellitus (DM) undergoing percutaneous coronary intervention (PCI) with everolimus‐eluting stents. Background: Second‐generation drug‐eluting stents have substantially improved outcomes after PCI in the general population; however, DM patients continue to experience high rates of ischemic and bleeding complications. Methods: DM patients from the pooled XIENCE V registry were divided into high or low bleeding and ischemic risk groups (HBR, LBR, HIR, and LIR) based on established bleeding (age ≥ 75 years; chronic kidney disease; anemia; prior stroke; oral anticoagulation; thrombocytopenia; prior major bleeding) and ischemic (acute coronary syndrome; prior myocardial infarction [MI]; ≥3 stents implanted; ≥3 vessels treated; ≥3 lesions treated; stent length > 60 mm; bifurcation treated with ≥2 stents; chronic total occlusion) risk factors. The primary outcomes were major adverse cardiac events (MACE; cardiac death, MI, or stent thrombosis) and major bleeding at 4‐year follow‐up. Results: A total of 3, 704 DM patients were divided into four groups (21.5% LBR/LIR; 39.0% LBR/HIR; 15.6% HBR/LIR; 23.9% HBR/HIR). Compared with LBR/LIR patients, those at HBR/HIR and HBR/LIR had a significantly higher risk of MACE (HR (95% CI) 2.7 (1.9–3.9) and 2.2 (1.5–3.2), respectively) and major bleeding (2.7 (1.6–4.8) and 2.6 (1.4–4.7), respectively), while LBR/HIR patients did not. Conclusions: Among DM patients undergoing PCI, presence of bleeding risk factors was associated with a higher risk of both ischemic and bleeding events, whereas commonly used features of ischemic risk did not impact long‐term clinical outcomes.